PUISI PEWARTAAN PARA NABI - Berthold Anton Pareira (Litbang STFT Widya Sasana Malang, 2004)
Reading poetry including that of the Bible is always a problem for many readers. The article intends to introduce the readers to the poetry of the prophets, to its distintive charactestics and to its soul. A good knowledge of the rhetoric of the prophets can be a great help for the formation of the present days servants of the word.